The strategic role of owners in firm growth: Contextualizing ownership competence in private firms - von Nitzsch, Jannis; Bird, Miriam; Saiedi, Ed (Strategic Entrepreneurship Journal, 2024)
Abstract Research Summary We integrate the emerging literature on the strategic role of firm owners in firms' value creation with Penrosean growth theory to investigate how and under what conditions two experience‐based competences among owners—matching competence and governance competence—influence firm growth. Employing a longitudinal sample of 2509 owner‐managed German firms, we find a positive relationship between owners' experience‐based competences and firm growth. Further, we find that in family firms, the positive relationship between owners' experience‐based governance competence and firm growth is weaker and that both experience‐based competences matter more in younger firms compared with older firms. Our findings make important contributions to research on strategic ownership and Penrosean growth theory. Managerial Summary In our study, we show that two competences of owner–managers are important for the growth of their firms: their matching competence, which is the ability to theorize about valuable resource configurations and cognitively envision a path to implement them, and their governance competence, which is the ability to create effective governance arrangements to align incentives within a firm. Our results suggest that it is challenging for owner–managers from family firms to leverage their governance competence to achieve growth, which could potentially be resolved by instituting governance mechanisms that prevent nepotism. We also show that owner–managers' competences are particularly important in the early years of their firms when no standardized processes are in place.